Sense spend: AI-enhanced financial apps for individuals with visual impairments - Mat Shah, Muhammad Hanif Ikmal; Ahmad Zawawi Wee, Mimie Hasanah; Amir Suhaimi, Amir Hafiy; Muhammad Ibrahim, Diyanah Insyirah; Mohamed, Munirah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
As more financial apps become available, there is a significant lack of accessibility features tailored to individuals with disabilities, especially those with visual impairments. Existing financial apps often overlook the specific needs of these individuals, making it challenging for them to manage their finances independently and efficiently. However, everyone deserves equal access to financial services. Unfortunately, people with disabilities often face exclusion, making it hard for them to access essential services. Therefore, innovation is growing needed to aid individuals with visual impairments in navigating financial apps. To address this need, we have developed a financial app with a user-friendly interface designed explicitly for people with visual impairments. We are upgrading our financial application framework with Artificial Intelligence (AI) to help those with disabilities in their daily life regarding financial transactions. Our innovative features are designed to empower users with visual impairments, giving them greater independence and autonomy in managing their financial affairs. By integrating advanced technologies such as Artificial Intelligence, our solution facilitates secure financial transactions and fosters confidence and efficiency among users with disabilities. Ultimately, our goal is to help people with disabilities access financial services. We aim to enhance accessibility features such as screen readers and virtual assistants, specifically designed to help meet the needs of individuals with visual impairments. As a result, we have decided to innovate a financial app for individuals with disabilities to facilitate financial transactions and enhance their overall user experience.